2022
DOI: 10.3389/fgene.2022.1007513
|View full text |Cite
|
Sign up to set email alerts
|

High temperature increased lignin contents of poplar (Populus spp) stem via inducing the synthesis caffeate and coniferaldehyde

Abstract: Lignin contributes to plant resistance to biotic and abiotic stresses and is dominantly regulated by enzymes which catalyze the generation of metabolites intermediates in lignin synthesis. However, the response of lignin and its key regulatory factors to high temperature stress are poorly understood. Here, this finding revealed that the content of lignin in poplar (Populus spp) stem increased after 3 days of high temperature stress treatment. In fourteen metabolic intermediates of lignin biosynthetic pathway w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…There are many intermediate metabolites involved in the lignin synthesis process. Previous research has pointed out that the content of these intermediate metabolites changes under abiotic stress [ 24 ]. Seven DAMs involved in lignin synthesis increased remarkably under salt stress in the root tissue of Sophora alopecuroides , including phenylalanine, cinnamic acid, ferulic acid, cinnamaldehyde, caffeylaldehyde, sinapyl alcohol, and coniferin [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many intermediate metabolites involved in the lignin synthesis process. Previous research has pointed out that the content of these intermediate metabolites changes under abiotic stress [ 24 ]. Seven DAMs involved in lignin synthesis increased remarkably under salt stress in the root tissue of Sophora alopecuroides , including phenylalanine, cinnamic acid, ferulic acid, cinnamaldehyde, caffeylaldehyde, sinapyl alcohol, and coniferin [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This facilitates the efficient long-distance transport of water, minerals, and organic matter within the plant. For instance, poplar increased the lignin biosynthesis in stem to cope with HT stress ( Zhao et al., 2022 ). In the transcriptome results of vascular bundle, phenylalanine metabolism pathway was significantly enriched in the HT treated group.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, intermediates of the lignin biosynthetic pathway, including caffeate and coniferaldehyde, increased in Populus spp. after exposure to HS (35°C) for 3 days (Zhao et al, 2022b). A study on tobacco revealed increased levels of sugars (sedoheptulose and sucrose) and non‐codogenic amino acids (pipecolate and c‐amino butyrate) at 22 and 37 °C, respectively (Krawczyk et al, 2022).…”
Section: Omics‐driven Breeding For Temperature‐smart Plantsmentioning
confidence: 99%